2013
DOI: 10.1007/s10856-013-5073-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of PHBHHx and PHBV/PLA fibers used as medical sutures

Abstract: Two types of fibers were prepared by using bio-based materials: a mono-filament made from poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) and a multi-filament made from poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and polylactic acid (PLA) blend. The two fibers were evaluated for mechanical properties, biocompatibility and degradability for the potential application as medical sutures. The PHBHHx fiber showed remarkable biocompatibility by H.E. Stainning, with very little impact to the surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…To overcome this, several environmentally friendly approaches have been proposed. One of this approaches is blending PLA with other polymers such as poly(hydroxy butyrate), PHB [11,2,12,13], poly(caprolactone), PCL [14], acetylated thermoplastic starch [15], etc. which can lead to tailored properties in terms of mechanical response, biodegradation rate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this, several environmentally friendly approaches have been proposed. One of this approaches is blending PLA with other polymers such as poly(hydroxy butyrate), PHB [11,2,12,13], poly(caprolactone), PCL [14], acetylated thermoplastic starch [15], etc. which can lead to tailored properties in terms of mechanical response, biodegradation rate, etc.…”
Section: Introductionmentioning
confidence: 99%
“…15 PHBV/Col nanofibers are promising substrates as bioengineered grafts for nerve tissue regeneration. 16,17 We previously described the inhibition of astrocyte activation by PHBV/PLA/Col membranes and revealed that the PHBV/PLA/Col-based scaffolds may be suitable for indirect transplantation after SCI. 18 Adjustment of experimental parameters and synthesis strategy allowed the optimization of the nanofiber morphology and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is a biodegradable polymer obtained from lactic acid, which has osteoconductive properties and has been used in various presentations. Although its applications were originally mainly in orthopedics (Athanasiou et al, 1998), for a long time it has been used in the craniofacial area for bone regeneration, as filling material in post-extraction alveolar preservation (Madan et al, 2014), as resorbable membrane in the treatment of periodontal bone lesions and guided bone regeneration (Kini et al, 2016;Rowe et al, 2016), as resorbable internal fixation to secure bone block grafts (Mazzonetto et al, 2010), as resorbable sutures (He et al, 2014) and as a carrier for growth factors and bone morphogenetic proteins (BMPs) (Ma et al, 2016), among others.…”
Section: Introductionmentioning
confidence: 99%